Silvinichthys pachonensis, a new catfish from high altitude, with a key to the species of the genus (Siluriformes: Trichomycteridae) - Fernandez, Luis Alfredo (2016)
Silvinichthys pachonensis, new species, is described from 3,103 m asl in the Andean cordillera of San Juan, Argentina, and constitutes the first record of the genus in high altitude. It shares the diagnostic characters of Silvinichthys, but is distinguished from the five named species mainly by the mesethmoid shaft larger that the side of the cornua (vs. shaft smaller than lateral cornua) and the relatively high number (14) of precaudal vertebrae (vs. 8 to 10 precaudal vertebrae). Additionally, it differs by the combination of a lack of the pelvic fin and girdle, strong abductor musculature, and various osteological, meristic, and morphometric features. Silvinichthys pachonensis is presently known only from the type locality, in an arid region of western central Argentina.